Surgical Retrieval of Esophageal Foreign Body in a Dog – A Case Report - Mahesh, V.; Ashok, H. N.; Sunil , C. L.; Nagaraja, B. N. (International Journal of Livestock Research, 2020)
A two and half month old Nondescript male puppy was presented with the clinical signs of hyper salivation, dysphagia, restlessness, and respiratory distress. A lateral cervical survey radiograph revealed a radio dense foreign body in the caudal cervical esophageal region. Esophagotomy was performed to remove the foreign body under general anesthesia. Esophagotomy wound was healed well and animal recovered uneventfully.